Aspekty polityczne i militarne „roku czterech cesarzy” (68-69 r. po Chr.). Część 1: do śmierci Galby - Kozłowski, Jakub; Królczyk, Krzysztof (Studia Europaea Gnesnensia, 2015)
The Year of the Four Emperors, as the period of civil wars in Rome after Nero’s death is often called, was the first major shake-up which affected the Roman state since a new system of rule, referred to as the Principate, had been established by Augustus. Following the imperial proclamation of Servius Sulpicius Galba, the governor of Spain (June 8th, 68) and the suicide of Nero (June 9th), the Roman state plunged into a profound political crisis. This was because the new emperor found no support either in the City itself, or among the soldiers of legions stationed on the Empire’s frontiers. On January 2nd, 69, Roman army on the Rhine hailed Aulus Vitellius, their commander, as the emperor. As Tacitus observed, this revealed the “secret of rule” (arcanum imperii) – namely one could become an emperor not only in the capital of the Empire but also on its remote periphery. Vitellius immediately began preparations for an armed contest with Galba. However, on January 15th, 69, the latter was murdered in Rome, and praetorians proclaimed M. Salvius Otho as the emperor.